2023
DOI: 10.1080/20008066.2023.2264612
|View full text |Cite
|
Sign up to set email alerts
|

Associations between individual cognitive factors, mode of exposure and depression symptoms in practitioners working with aversive crime material

Fazeelat Duran,
Jessica Woodhams

Abstract: Background: There is extensive literature on front-line officers and investigators exposure to trauma and its negative impact on them. However, there are analytical practitioners in law enforcement who indirectly work with the traumatic experiences of other people daily, but are seldom the focus of academic research. Objective: Our goal was to conduct the first international study with these practitioners to identify the risk of depression symptoms and establish whether poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
0
0
Order By: Relevance
“…Similar adverse outcomes have been found for staff working in other investigative functions. For example, Duran and Woodhams (2023) surveyed crime analysts and secondary investigators across the UK, Europe and Canada and found that 52% of respondents scored within the range for moderate depression. Depressive symptoms were found to be positively associated with the vividness of mental imagery, believing in a just world, thought suppression, and the exposure being through combined audio and visual functions.…”
Section: Secondary Exposure To Trauma In Police Staffmentioning
confidence: 99%
“…Similar adverse outcomes have been found for staff working in other investigative functions. For example, Duran and Woodhams (2023) surveyed crime analysts and secondary investigators across the UK, Europe and Canada and found that 52% of respondents scored within the range for moderate depression. Depressive symptoms were found to be positively associated with the vividness of mental imagery, believing in a just world, thought suppression, and the exposure being through combined audio and visual functions.…”
Section: Secondary Exposure To Trauma In Police Staffmentioning
confidence: 99%